Penyelesaian Sengketa Pemilihan Kepala Desa Menurut Undang-Undang Nomor 6 Tahun 2014 Tentang Desa dan Fiqih Siyasah (Studi Kasus di Desa Sukaslamet Kecamatan Kroya Kabupaten Indramayu) - Ikmal, Muhammad; Rohmah, Siti Ngainnur; Mufidah, Mufidah (SALAM: Jurnal Sosial dan Budaya Syar-i, 2023)
The Village Head Election aims to elect a leader from the village community. There are winners and losers in this process, but not all defeats can be accepted sincerely, with an open heart, and make the village head election a normal process in every leadership change. Few participants or supporters accepted defeat in the village head election, with various reasons or excuses, including feeling disadvantaged by the results obtained, cheating, or even money politics. The rejection of the results of the village head election must lead to a conflict between supporters that has not been resolved, and even the losing party in the village head election filed an objection or dispute over the results of the village head election according to existing procedures according to laws and regulations. The method used in this study is qualitative with a conceptual approach. The study results show that the mechanism for electing the village head in Sukaslamet Village is voting, and several TPSs receive direct monitoring from the Ministry of Home Affairs, even the deputy governor of West Java. In the process of resolving disputes over the results of the Village Head election in Sukaslamet Village, the provisions according to Law Number 6 of 2014 concerning Villages, Article 37 paragraph (6) are that in the event of a dispute over the results of the Village Head election, the Regent or Mayor is required to resolve the dispute within 30 days from the receipt of the lawsuit report.Keywords: Dispute Resolution; Village Head Election; Fiqh Siyasah AbstrakPemilihan Kepala Desa bertujuan untuk memilih pemimpin yang berasal dari masyarakat desa. Dalam proses ini pun tentu ada yang menang dan ada pula yang kalah, akan tetapi tak semua kekalahan itu bisa diterima dengan ikhlas, dengan hati lapang dada, dan menjadikan pilkades adalah proses yang biasa dalam setiap pergantian kepemimpinan. Tidak sedikit pula peserta atau pendukung yang tidak menerima akan kekalahan dalam pilkades, dengan berbagai sebab atau alasan diantaranya adalah merasa dirugikan dengan hasil yang diperolehnya, ada kecurangan atau bahkan ada politik uang. Ketidakterimaan atas hasil pilkades tersebut harus berujung pada konflik antar pendukung yang tak kunjung selesai, dan bahkan terhadap pihak yang kalah dalam pilkades mengajukan keberatan atau sengketa hasil pilkades sesuai prosedur yang ada menurut peraturan perundang-undangan. Metode yang digunakan dalam penelitian ini adalah kualitatif dengan pendekatan konseptual. Hasil penelitian menunjukkan bahwa mekanisme pemilihan Kepala Desa di Desa Sukaslamet adalah dengan pemungutan suara, beberapa TPS mendapat monitoring langsung dari Kemendagri, bahkan juga Wakil Gubernur Jawa Barat.Kata Kunci: Penyelesaian Sengketa; Pemilihan Kepala Desa; Fiqih Siyasah